Development of Augmented Reality-Based Mobile App Learning Media for Computer Network Hardware Material - Ashabul Taufik; Nur Alamsyah; Andika Saputra (PT ARRUS Intelektual Indonesia, 2023)
The objective of this research is to create a mobile app-based augmented reality learning media for computer network hardware. The specific aims are to describe the application model design, application functionality, feasibility, and effectiveness of using augmented reality-based mobile app learning media on computer network hardware. The research methodology employed in this study is Research and Development (R&D). The development stages include research, data collection, planning, draft product development, product validation, revision based on product validation results, field testing, revision based on field testing results, final product refinement, and dissemination. Furthermore, to assess the improvement in learning outcomes, the Independent Sample T Test statistical method is used. The results obtained in this research show a significant difference in the experimental class compared to the control class, where the average score in the experimental class is higher. Therefore, it can be concluded that learning computer network hardware material using augmented reality has successfully improved student learning outcomes. Keywords: Learning Media, Augmented Reality, Mobile Apps, Computer Network Hardware.